Utilizing Pterocarpus marsupium Rox.b Heartwood Extract for Green Synthesis of Magnesium Oxide Nanoparticles: Exploring Biomedical Applications and Beyond (International Journal of Food and Nutritional Sciences, 2021)
This study aimed to synthesize magnesium oxide nanoparticles (MgO-NPs) by employing an aqueous extract derived from the heartwood of Pterocarpus marsupium [1] . The heartwood extract of Pterocarpus marsupium is abundant in polyphenolic compounds and flavonoid [2], making it a sustainable and eco-friendly source for the large-scale production of MgO-NPs. The phytoassisted synthesis of MgO-NPs was characterized using various techniques, including UV-Visible spectroscopy [3], X-ray diffraction (XRD), dynamic light scattering (DLS), Fourier transform infrared spectroscopy (FT-IR) [4], scanning electron microscopy (SEM) with energy dispersive X-ray spectroscopy (EDS) [5], and transmission electron microscopy (TEM) [6].